(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This article focuses on the dismantling of reproductive rights occurred during the Trump administration. First, it highlights the connections between pro-life extremism, white supremacism and the anti-governmental right. Next, the article showcases how, under Trump, from social movements, arguments against reproductive rights based on false science and gender-based stereotypes have become the rationale of policies, laws and judicial decisions. The article concludes that the attack on reproductive rights was part and parcel of the Trump’s administration’s project to influence human rights epistemology and the ways in which such rights are conceptualized and applied both domestically and internationally.